Quantitative EEG provides early prediction of poor outcome in acute ischemic stroke after endovascular treatment: a preliminary study. (3rd October 2021) - Wang, Yunfeng; Liu, Dacheng; Liu, Jingyi; Kong, Chaohong; Zhang, Zhe; Duan, Wanying; Dornbos, David; Liu, Liping
ABSTRACT: Background and Purpose : Quantitative electroencephalogram (QEEG) parameters have been previously utilized in prognosis following acute ischemic stroke (AIS). However, the use and interpretation of QEEG parameters remain scarce following endovascular treatment (EVT) of AIS. Methods: AIS patients were prospectively enrolled following EVT, and 24-hour EEG monitoring was conducted. Global delta/alpha ratio (DAR), (delta + theta)/(alpha + beta) ratio (DTABR), and relative band power were analyzed. Primary outcome was a poor outcome (modified Rankin Scale ≥4 at 90-day follow-up). Multivariate logistic regression and diagnostic analyses were performed. Results: Poor outcome was seen in 35.5% (11/31) of enrolled patients. Multivariable logistic regression identified that higher DAR (OR 1.10, 95% CI 1.02–1.18, p = 0.02) and higher DTABR (OR 1.13, 95% CI 1.01–1.27, p = 0.02) were associated with poor outcome. DAR ≥14.3 demonstrated high sensitivity (90.9%), specificity (90.0%) and accuracy (90.3%) for poor outcome. Conclusions: Early evidence of elevated DAR and DTABR on quantitative EEG was associated with poor outcome at 90 days following EVT for AIS.